"I Avenge; Others Aggress": A Victim–Perpetrator Asymmetry in Judging Whether a Transgression Was Motivated by Revenge. Issue 4 (August 2020) - Ent, Michael R.; Parton, Drew M.
In two studies, victims differed from perpetrators as to whether they viewed a transgression as motivated by a desire for revenge. When participants wrote about autobiographical episodes in which they hurt others, they were somewhat likely to report that they were motivated by revenge; when the same participants wrote about episodes in which others hurt them, they were less likely to report that the perpetrators were motivated by revenge. This asymmetry could act as a barrier to reconciliation. This asymmetry may also facilitate a cycle of revenge in that those who view themselves as the targets of unprovoked aggression (as opposed to vengeance) may be especially likely to feel that they have a score to settle.